2005
DOI: 10.1172/jci23409
|View full text |Cite
|
Sign up to set email alerts
|

In vivo measurements document the dynamic cellular kinetics of chronic lymphocytic leukemia B cells

Abstract: Due to its relatively slow clinical progression, B cell chronic lymphocytic leukemia (B-CLL) is classically described as a disease of accumulation rather than proliferation. However, evidence for various forms of clonal evolution suggests that B-CLL clones may be more dynamic than previously assumed. We used a nonradioactive, stable isotopic labeling method to measure B-CLL cell kinetics in vivo. Nineteen patients drank an aliquot of deuterated water ( 2 H 2 O) daily for 84 days, and 2 H incorporation into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
219
1
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 518 publications
(238 citation statements)
references
References 37 publications
11
219
1
7
Order By: Relevance
“…In an analysis by Messmer et al [3] it was demonstrated that the leukemic cells of each patient had definable birth rates and those patients with higher birth rates were much more likely to exhibit progressive disease than these with lower birth rates. A correlation between birth rates and disease activity appears to exist that may help to identify patients at risk for worsening disease and in advance of clinical deterioration [3]. The CD38-positive fraction is more active than the CD38-negative counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an analysis by Messmer et al [3] it was demonstrated that the leukemic cells of each patient had definable birth rates and those patients with higher birth rates were much more likely to exhibit progressive disease than these with lower birth rates. A correlation between birth rates and disease activity appears to exist that may help to identify patients at risk for worsening disease and in advance of clinical deterioration [3]. The CD38-positive fraction is more active than the CD38-negative counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…In advanced stage CLL patients, a clone of malignant cells previously arrested in G₀/G 1 may evolve into an actively proliferating population [24]. Cell proliferation and death rates differ considerably among CLL patients, and the level of CLL turnover is important for the natural history of the progression of the disease in an individual patient, which can have significant clinical implications [3,23]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an approach our group has previously applied to identify causal pathway BMs in other conditions, such as neurodegeneration (Fanara et al ., 2012), fibrotic disease (Decaris et al ., 2015), and cancer (Messmer et al ., 2005). The concept underlying this strategy is that the activity of a metabolic process is best characterized by the molecular flux rate traversing the pathway and that changes in the flux rates of metabolic processes that play a causal role in the functional alterations of the condition may manifest earlier and more sensitively than static pathologic changes or complex clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, CLL was considered to result from the accumulation of long‐lived, but resting lymphocytes; however, recent evidence points to the presence of a pool of proliferating B cells 1. Clinically, CLL is a very heterogeneous disease; many patients require no therapy and show an asymptomatic disease, while other patients suffer from a rapidly progressing disease despite treatment.…”
Section: Introductionmentioning
confidence: 99%